2020
DOI: 10.1021/acs.orglett.0c01260
|View full text |Cite
|
Sign up to set email alerts
|

The C–H Activation/Bidirecting Group Strategy for Selective Direct Synthesis of Diverse 1,1′-Biisoquinolines

Abstract: Multidentate ligands are highly important but difficult to access. Herein we disclose an atom- and step-economic synthesis of highly substituted 1,1′-biisoquinolines by a C–H activation/bididirecting group strategy. Through rational design of a bididirecting group to “N–OH + N–OAc”, selective unsymmetrical diannulation with two different alkynes in a one-pot reaction has been achieved for the first time to access unsymmetrical biisoquinolines. Moreover, the resultant biisoquinolines show tunable photoluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…24 Gratifyingly, by treatment of 1-E with 2 molecules of alkyne, 1,1′-bisisoquinolines 8a and 8b could be efficiently obtained in fair yields through an unprecedented ring-opening, decarbonylative double C-H annulation, which serves as a complementary method to our previous work. 25 These results revealed that both the C4 and C5 aryls can be activated when the imidazole ring is destroyed.…”
Section: Resultsmentioning
confidence: 89%
“…24 Gratifyingly, by treatment of 1-E with 2 molecules of alkyne, 1,1′-bisisoquinolines 8a and 8b could be efficiently obtained in fair yields through an unprecedented ring-opening, decarbonylative double C-H annulation, which serves as a complementary method to our previous work. 25 These results revealed that both the C4 and C5 aryls can be activated when the imidazole ring is destroyed.…”
Section: Resultsmentioning
confidence: 89%
“…A plausible mechanism is proposed on the basis of preliminary mechanistic experiments and literature precedents. [18] As shown in Scheme 5, the five-membered rhodacycle A intermediate was formed by coordination, and undergoes CÀ H bond cleavage at the C5 position. For ketone substrate, the rhodacycle A could convert into intermediate B through the transmetalation with 2 a, then the reductive elimination of intermediate B gives rise to the desired product 3 aa and Rh I species.…”
Section: Resultsmentioning
confidence: 99%
“…Unless otherwise noted, all reagents and solvents were obtained from commercial suppliers such as Aladdin, Beijing Innochem Chemical Engineering Reagent (China) Co., Ltd., Energy Chemical, etc., and used without further purification. [(Cp*RhCl 2 ) 2 ] alkynes and [D 10 ]- 1a were prepared according to the literature procedures. Unless otherwise noted, all reaction mixtures were heated with aluminum heating blocks and detected by TLC (thin layer chromatography) with silica gel-coated plates.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the fact that they are valuable examples of BIQ synthesis, they cannot be shown to synthesize 1,1′-BIQs, and extra steps are needed to install the DGs. Recently, our group reported a C–H activation/bidirecting group strategy for producing 1,1′-BIQs from Z,Z -type dioximes and alkynes (Scheme b); however, Z,Z -type dioximes need extra preparation, and other undesired Z,E - and E,E -type isomers may be generated. Herein, we further pave the way for the synthesis of 1,1′-BIQs through a three-component reaction of commercially available raw materials, benzils, ammonium acetate, and alkynes (Scheme c).…”
Section: Introductionmentioning
confidence: 99%